Image and image production between Vedic India and Platonism : una “forma” (eîdos) di prassi comparativa - Rossi, Paola M. (Scenari, 2021)
Some considerations about the debated issue of “image” and “imaging” are here proposed, taking into account a comparative perspective, interpreted as epistemological approach, according to the definition of “comparative practices” by G. Pasqualotto. In this case, the well-known Platonic conception of “image” will be considered through the “Other” gaze of the Vedic culture, which characterized the Indian civilization between 1500 and 500 BCE. Comparing Platonic “image” and “imaging” with Vedic “image” and “imaging” would not mean that they are two antithetic modality of representing reality, but, both can be considered as two stages of the same conception of creating process. The Vedic “imaging” is the generating and cosmogonic act, caught directly in performing as ritual practice; the Platonic “imaging” is the creating act as reflected through the theorising effort. Both are mutually implied: the ontological hierarchy resulting from the theoretical conceptualization of generative acts entails the originating event as paradigmatic act. Nonetheless, the paradigmatic generative act is being kept as active and performing only if it reduplicates itself, as auto-generative ritual act. Therefore, creating act and theorising act are combined in imaging.